The development and validation of a quality of life assessment instrument for cancer patients in South Africa - Van Rensburg, Jacoba Johanna Maria Jansen (My University, 2016)
Background: Quality of life (QoL) of cancer patients has been well researched, but not necessarily from the perspective of the patient and not in third world countries. Total care of cancer patients should encompass all aspects of the person, such as physical-, psychological- and social aspects, existential wellbeing and spirituality, in order to ensure optimal QoL. The purpose of the study was to explore QoL from the perspective of the cancer patient who accesses public health care services in South Africa for treatment and to develop and validate an appropriate patient-directed assessment instrument. Method: The study was conducted in two phases. In Phase 1 assessment of QoL was done by means of in-depth qualitative interviews. Open coding and template analysis was conducted \during data analysis and the applicable domains of QoL were identified. In Phase 2 an appropriate QoL assessment instrument was developed for cancer patients in South Africa. The Rasch Measurement Model was utilized for the validation of the instrument. Results: The domains of QoL identified by the cancer patients were: physical, psychosocial, financial, spiritual, existential and emotional. When compared with the domains included in available QoL assessment instruments such as the World Health Organization Quality of Life Instrument (shortened version) (WHOQOL-BREF), the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and the Functional Assessment of Cancer Therapy General (FACT-G), the domains identified by cancer patients in South Africa were not fully addressed by these instruments. Significance of results: Culture, psychosocial status, financial aspects and spirituality play a major role in QoL of South African patients, as indicated by this study as well as a previous study on QoL of palliative patients from a resource-poor community in South Africa. These aspects of QoL are not addressed by the most commonly used assessment instruments. The importance of the utilization of an instrument which addresses all the appropriate domains of QoL is highlighted by the study.
A thesis submitted to the Faculty of Health Sciences. University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2016
Keywords: Quality of Life; Neoplasms